Pengembangan E-Modul Berbasis Potensi Lokal Berbantuan Google Sites untuk Mengembangkan LITERASI SAINS SISWA: The Development of Local Potential-Based E-Module Assisted by Google Sites to Develop Students’ Science Literacy - Rindy Dwita Ayu Lestari; Sri Wahyuni; Zainur Rasyid Ridlo (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2024)
Science literacy skill is one of the 21st-century skills that a person must master to adapt to the changing dynamics of life. However, the level of science literacy among students in Indonesia remains low. Therefore, this research develops e-module that utilizes the potential of Kemiri Village to enhance students' science literacy skill. This research aims to describe the validity and readability of local potential-based e-module. The stages of e-module development are adapted from the ADDIE model, but only up to the development stage. The subjects of this research consist of 3 science teachers and 10 ninth-grade students from SMP Negeri 1 Panti. Based on the results of the validity test, the local potential-based e-module has a very valid category with content and construct validity percentages of 89.58% and 92.16%, respectively. The readability level of this e-module is also very good with a percentage of 90.94%. From the research conducted, it can be concluded that the local potential-based e-module is easy to understand and suitable for application in the science learning process.